Dynamics Resilience of Female Influencer as NCII Victim on Social Media - Almira, Nabila Sella; Wahyuni, Lilik; Ratnawati, Retty (Sekolah Pascasarjana Universitas Brawijaya, 2024)
The widespread distribution of non-consensual intimate content carried out by the increasing development of technology cannot be stopped. Komnas Perempuan recorded 281 cases of cybercrime out of 1,277 cases of gender-based violence reported in 2021, which experienced an increase in CATAHU Komnas Perempuan 2023, where there were 869 cases of cyberviolence out of 1,276 cases of gender-based violence. Technological developments can make it easier for someone to commit cyber crimes. On the other hand, this technological development influences the rapid dissemination of information, especially with the mass presence of influencers. Influencers are social media users who generally come from ordinary people who have succeeded in gathering large numbers of followers so they can monetize their influence. However, influencers also have dangerous risks, in which one of them is vulnerable to becoming a victim of NCII with how often they use social media to show their face, body, and even voice. Non-consensual dissemination of intimate images (NCII) is a cybercrime where the use of intimate or sexual content for threats. This research aims to analyze the resilience of female influencers who have experienced NCII threats. This research used the qualitative method. The data used interviews with influencers who have experienced NCII but choose to continue their career. The results show that the subject’s resilience came from external support from family and peers, revenge for the perpetrator, and religiosity. Legal action and official protection against the threat of NCII are necessary to prevent the increase in victims.Keywords: dynamics of resilience, cybercrime, female influencer, NCII